(untitled) (Research, Society and Development, 2023)
Objectives: To evaluate the prevalence and associated symptoms of cerumen impaction in adults in the state of Rio Grande do Norte. Methods: This is an analytical, cross-sectional and observational research, with a quantitative approach, in which users, companions and employees of a tertiary hospital aged 18 years or older participated, through otoscopy and evaluation of clinical otological complaints. Results: 1,067 adults aged between 18 and 87 participated, 64.9% (n=692) were women and 35.1% (n=375) were men. Among them, 11.6% (n=124) had earwax impaction in one of the ears and 90.3% (n=963) had earwax in at least one ear. Conclusion: The prevalence of cerumen impaction in the study was significantly higher than in similar literature and it was shown to be an issue related to “using a flexible swab with cotton-tipped tips” and “having had previous ear washing”. Otoscopy remains as the gold standard for the mostly asymptomatic clinic of patients with wax plugs.